Gold as a Systemic Safe Haven Amid Global Economic Uncertainty in G20 Countries - Ahmad Saifi Athoillah Athoillah; Dwi Rahma Fitriani; Mutia Tsalitsa Alawia; Dion Yanuarmawan; Yohan Bakhtiar; Wiwik Mukholafatul Farida (Sean Institute, 2026)
The escalation of global economic uncertainty driven by financial crises, geopolitical tensions, and monetary policy tightening has reignited debates regarding the role of gold as a value-preserving asset within the global financial system. Although prior studies have extensively examined gold as a hedging instrument and safe haven asset, empirical evidence concerning its ability to function as a systemic safe haven particularly under conditions of extreme risk, crisis regime dynamics, and cross-market interconnectedness remains limited and inconclusive, especially within G20 countries characterized by high levels of financial integration. This study aims to investigate whether gold serves as a systemic safe haven during periods of global economic uncertainty by emphasizing the dimensions of tail risk, crisis regimes, and risk transmission across financial markets. The study employs monthly panel data from G20 countries over the period 2000–2024 obtained from open-access databases, including global gold prices, the Global Economic Policy Uncertainty (GEPU) Index, the Volatility Index (VIX), global financial stress indicators, exchange rates, stock market indices, and government bond yields. To capture nonlinear relationships and extreme dependence structures, this research adopts advanced econometric approaches combining Markov-Switching Quantile Vector Autoregression and connectedness analysis. The empirical findings reveal that gold significantly functions as a systemic safe haven at the lower quantiles of financial market return distributions, particularly during periods of crisis and heightened uncertainty. Furthermore, gold tends to act as a shock absorber within cross-market connectedness networks, thereby contributing to the stability of financial systems across G20 countries. These findings enrich the existing literature by offering a systemic safe haven perspective and provide important policy implications for monetary authorities and foreign reserve managers in designing global financial resilience strategies.